Pengaruh Kemampuan High Order Thinking Skill Terhadap Hasil Belajar Matematika Siswa Kota Parepare - Wulan Dari (Tautologi: Journal of Mathematics Education, 2023)
This study aims to determine the effect of High Order Thinking Skill on the mathematics learning outcomes of students in class XI UPT SMA Negeri 1 Parepare, while this type of research is quantitative research using the Ex Post Facto approach. The population of this study were all social studies students of class XI UPT SMA Negeri 1 Parepare. The sample in this study amounted to 30 respondents by using a sampling technique is Cluster Random Sampling. The research data was obtained using a research instrument in the form of a description test sheet of 2 numbers to determine the HOTS ability and student learning outcomes. The data collection technique used is a test technique. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis of students of class XI IPS UPT SMA Negeri 1 Parepare were 30 respondents where the students' HOTS ability was in the high category with an average student of 74.83 and a standard deviation of 19.84. The score of students' mathematics learning outcomes is in the medium category with an average student mathematics learning outcome of 76.33 and a standard deviation of 20.08. There is a positive significant effect of HOTS ability on mathematics learning outcomes for students of class XI IPS UPT SMA Negeri 1 Parepare at a significant level = 0.05